Emergency economic powers of the U.S. President - PENDERS , PJ; CUI, Jonathan (Journal of Economics Library, 2024)
Abstract. This paper examines the emergency economic powers of the President in the United States. The paper discusses the various powers that the President can invoke in times of economic crisis, including the authority to implement tariffs, regulate international trade, and control prices. An accompanying spreadsheet lists all those powers plus some additional powers that are not mentioned in the main text. The purpose of this paper is to provide a comprehensive overview of the economic emergency powers of the President and to serve as a resource for policymakers and scholars who are interested in this topic. Keywords. Emergency powers; President; United States. JEL. H11; H12.